Study on Market Supply of Rural Public Sports Service in China - Zhu, Wanjing (Asian agricultural research, 2015)
In the main trend of gradually improving socialist market economy and establishing public service type government,market supply of rural public sports service is necessary. On the basis of unique characteristics of China’s rural society and market experience of domestic and foreign public service,market supply methods were discussed about rural public sports service. However,there are certain factors restricting market supply in this process. On the basis of the analysis,it came up with several optimization measures for market supply of rural public sports service.